Standardization of an analytical method to quantify ochratoxin A in green coffee beans by high performance liquid chromatography (Research, Society and Development, 2020)
Nowadays, Brazil is the largest producer and exporter of coffee, also the second largest consumer of the beverage. The importance of ensuring food safety for consumers has influenced research to improve and monitor the final product quality. Coffee is a product that presents a high risk of fungal contamination, which can result in the presence of mycotoxins and poses risks to human and animal health. Therefore, this study aimed to standardize a chromatographic method to test and quantify ochratoxin A in 13 samples of green coffee beans. The green coffee beans were stored in sheds without temperature or humidity control. Samples were ground, and the analyte was extracted by a 3% methanol:sodium bicarbonate (1:2 v/v) solution. Ochratoxin A was quantified in a high performance liquid chromatograph. The method was validated by testing the selectivity, linearity, accuracy, limits of detection and quantification. The method presented robustness to the tested parameters and among the analyzed samples. Ochratoxin A was detected above the limit established by the legislation (75.19 µg kg-1) only in one sample. Overall, the storage of green coffee beans in these sheds was adequate, since 12 samples had a low content of ochratoxin A and they were within the limit established by legislation. Therefore, food safety was guaranteed without any severe mycotoxin contamination.